STATUS PERNIKAHAN DAN DUKUNGAN SOSIAL SUAMI TERHADAP KUALITAS HIDUP WANITA MENOPAUSE DI KOTA PALANGKA RAYA - Itma Annah; Harlyanti Muthma’innah Mashar (LPPM STIKES Muhammadiyah Kendal, 2020)
Menopause is a period of permanent cessation of the menstrual cycle, causing decreased production of the hormones estrogen, progesterone and testosterone. Some of the symptoms of menopause are hot flashes, night sweats, and vaginal atrophy resulting in vaginal dryness associated with changes in sex hormone levels resulting in decreased quality of life for menopausal women. The purpose of this study is to look at the relationship between marital status and husband's social support to the quality of life of menopausal women in Palangka Raya City. The instrument used to assess the quality of life of menopausal women is to use The Utian Quality of Life (UQOL) Scale. The research method used is a cross sectional study design. The results showed there was a relationship between marital status and the quality of life of menopausal women (p = 0,000), as well as husband's social support (p = 0,000). Therefore, it is very important that there is family support especially the husband in providing social support for menopausal women.